2018
DOI: 10.1111/jcpp.12987
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic trajectories of dimensional psychopathology across the lifespan: the case of youth‐onset attention deficit/hyperactivity disorder

Abstract: Background Recent studies have demonstrated the existence of a distinct late‐onset attention deficit/hyperactivity disorder (ADHD) trajectory. Our objective is to test if there are distinct ADHD trajectories regarding age of onset from childhood to adolescence and to compare clinical manifestations, cognitive functions and genetic risk for ADHD among distinct longitudinal groups. Method Nine hundred and twenty four children and adolescents from the community participated in the study. We compared clinical, cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…These individuals would not meet current diagnostic criteria for ADHD if their age-at-onset was known and the discovery of this group challenges the conceptualization of ADHD as a neurodevelopmental disorder. Three studies investigating "late-onset" ADHD have not observed associations with ADHD PRS, although these have been limited in power due to sample size [44,47,48]. Thus, while childhood and persistent ADHD appear to be genetically similar, this may not be the case for "late-onset" ADHD.…”
Section: Adhd: What Happens Over Timementioning
confidence: 99%
“…These individuals would not meet current diagnostic criteria for ADHD if their age-at-onset was known and the discovery of this group challenges the conceptualization of ADHD as a neurodevelopmental disorder. Three studies investigating "late-onset" ADHD have not observed associations with ADHD PRS, although these have been limited in power due to sample size [44,47,48]. Thus, while childhood and persistent ADHD appear to be genetically similar, this may not be the case for "late-onset" ADHD.…”
Section: Adhd: What Happens Over Timementioning
confidence: 99%
“…The Brazilian High‐Risk Cohort is a school‐based community cohort of 2,511 children (1,554 high‐risk and 957 randomly selected (Salum et al., )) who received psychiatric evaluations at baseline and after three‐year follow‐up with the DAWBA administered to parents. Restricting to participants who were less than age 12 at baseline and older than age 12 at follow‐up, this study identified community comparisons ( n = 806) who had no more than two ADHD symptoms at baseline or follow‐up (and no other psychiatric disorder at baseline), childhood‐limited ADHD ( n = 64) who met ADHD diagnostic criteria at baseline and had no more than two ADHD symptoms at follow‐up, persistent ADHD ( n = 26) who met ADHD criteria both in childhood and at follow‐up, and youth‐onset ADHD ( n = 28) who had no more than two ADHD symptoms at baseline and met ADHD criteria at follow‐up (Manfro et al., ). The mean age at baseline for these groups ranged from 9.8–10.1 years and at follow‐up from 13.1–13.6 years.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Nearly half of the young adult ADHD group, as identified by parent report, did not meet borderline criteria for ADHD at age 7 (Riglin et al., ); and 25.3% of late‐onset individuals had low to average ADHD symptoms across all childhood assessments up through age 12 (Cooper et al., ). Additionally, in the Brazilian High‐Risk Study parent‐report was used both in childhood and adolescence and found about half of those who met full ADHD criteria in young adulthood were late‐onset (Manfro et al., ). Therefore, it seems we can safely conclude that the change in rater from parent to self does not completely account for those individuals with apparent onset of ADHD after childhood.…”
Section: Possible Explanations For Late‐onset Adhdmentioning
confidence: 99%
“…Manfro et al. contribute to a fascinating (and growing) literature on youth‐onset ADHD, that is, the observation that a subtype of ADHD starts in adolescence (Manfro et al., ). By exploring general psychopathology scores in childhood and adolescence, Manfro et al.…”
Section: The P Factor As An Essential Covariate In Studies Of Specifimentioning
confidence: 99%